The impact of ESG scores on the firm value - evidence from the Airline industry - Hartmann, Simon Philipp (2022)
The group part of the airline industry report investigates which airlines are best positioned to operate in a sustainable post- Covid market environment. The results show that low-cost carriers are likely to emerge as the leading business model in the future. This individual part of the airline industry report investigates the impact of the ESG scores and the individual environmental, social, and governance scores of airlines on the firm value of the industry report peers. Furthermore, the performed regression shows a positive influence for the ESG, the social, and the governance scores, mean while the environmental score has a negative influence.